Penggunaan model example nonexample untuk meningkatkan keterampilan menulis teks deskripsi pada peserta didik kelas V sekolah dasar - Majiid, Sony Perdana Ahmad Nur; Winarni, Retno; Sriyanto, Muhammad Ismail (Didaktika Dwija Indria, 2020)
This study aims to improve the skills of writing descriptive text using the Example Nonexample model. The subjects of this study were 21 fifth grade students of Bumi I Elementary School in 2019/2020. This study uses data collection techniques such as observation, interviews, documentation and writing skills tests that are tested with content validity, triangulation of data sources and triangulation techniques. The results obtained will be processed by data analysis techniques from Miles and Huberman. From the results before applying the Example Nonexample model, classical completeness was only 5 students (23.8%), then after applying the Example Nonexample model the results of writing description text skills increased by 12 students (57.2%) in the first cycle and 18 students (85.7%) in the second cycle. So, the Example Nonexample model can improve description writing skills in fifth grade students of Bumi I Elementary School in 2019/2020 school year. The teacher can use the Example Nonexample model in learning to write description texts especially in the fifth grade of Bumi I Elementary School.